Ruxolitinib and pegylated interferon in Chronic Neutrophilic Leukemia due to a pathogenic CSF3R germline variant: a case report - Grano, Selene; Bonuomo, Valentina; Carli, Diana; Peri, Veronica; Farinasso, Loredana; Ramenghi, Ugo; Cilloni, Daniela; Fava, Carmen (Frontiers in Hematology, 2024)
Chronic neutrophilic leukemia (CNL) is a rare myeloproliferative neoplasm characterized by CSF3R mutations. Here, we report the first case of a CNL patient positive for a de-novo germline CSF3R T618I variant effectively treated with ruxolitinib and pegylated interferon (peg-IFN), obtaining normalization of blood counts and maintaining good disease control for over 8 years. In addition, the RUNX1 L56S variant was detected at diagnosis and confirmed in subsequent next-generation sequencing (variant allele frequency of 50.4%). Although this variant has been debated, it is now widely recognized as a benign polymorphism and current evidence shows it does not modify prognosis. Our report adds to the growing body of evidence confirming the importance of a good evaluation of the mutational status of driver mutations in the setting of germline variants.